2004
DOI: 10.1016/j.jasms.2004.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the binding stoichiometries of positively charged DNA-binding drugs using positive and negative ion electrospray ionization mass spectrometry

Abstract: dpqC]Cl 2 with DNA, highlighting the need for obtaining ESI mass spectra of non-covalent complexes under a range of experimental conditions. Negative ion spectra of mixtures of the minor groove binder Hoechst 33258 with DNA containing a known minor groove binding sequence were dominated by ions from a 1:1 complex. In contrast, in positive ion spectra there were also ions present from a 2:1 (Hoechst 33258: DNA) complex, suggesting an alternative binding mode was possible either in solution or in the gas phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…All results presented here demonstrate that there are neither false positives, nor false negatives in the complexes observed in negative ion mode ESI-MS. In positive ion mode, there may be some false negatives, as has been shown by Sheil and coworkers [20,21] and in the present work for the intercalators that bind to duplex DNA exclusively by stacking interactions. At the most, positive ion mode could be used, when a complex is detected in negative ion mode, to test whether the complex involved purely stacking interactions or whether there are other hydrogen bonding interactions remaining.…”
Section: On the Use Of Positive Ion Mode Esi-mssupporting
confidence: 57%
See 1 more Smart Citation
“…All results presented here demonstrate that there are neither false positives, nor false negatives in the complexes observed in negative ion mode ESI-MS. In positive ion mode, there may be some false negatives, as has been shown by Sheil and coworkers [20,21] and in the present work for the intercalators that bind to duplex DNA exclusively by stacking interactions. At the most, positive ion mode could be used, when a complex is detected in negative ion mode, to test whether the complex involved purely stacking interactions or whether there are other hydrogen bonding interactions remaining.…”
Section: On the Use Of Positive Ion Mode Esi-mssupporting
confidence: 57%
“…Several papers demonstrated that this approach gives reliable apparent binding constants in the case of duplex DNA [15,16], quadruplex DNA [17], and different RNA structures [18,19]. Some papers were recently published on ESI mass spectra of DNA acquired using positive ion mode [20,21]. We therefore wanted to assess whether the positive ion spectra are likely to provide an accurate picture of the drug-DNA complexes present in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the DNA-binding affinities of the APs obtained by ESI-MS screening correlated with their inhibitory activities. ESI-MS has also been used to evaluate the complexation of other types of novel ligands (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), including acridines (31), cationic porphyrins (36), cryptolepine alkaloids (37), protoberbine alkaloids (38), benzopyridoindole and benzopyridoquinoxaline compounds (32), and acridine-and naphthalene-derived macrocyclic bis-intercalators (33), with DNA duplexes.…”
Section: Figurementioning
confidence: 99%
“…There have been numerous ESI-MS studies that have examined the interaction between duplex DNA and well-studied, commercially available mono-intercalators such as the anthracyclines [6][7][8][9][10][11], porphyrins [12,13], ruthenium compounds [11][12][13][14][15], ethidium bromide [16][17][18], actinomycin-D [12,13], and aureolic acids [19]. Characteristics such as ligand binding stoichiometry [7,8,[11][12][13][14]16], sequence selectivity [7,11,13,14,16,19], binding mode [12,13,15] and complex stability [9,12,16] have been examined with promising results correlating the binding trends observed in the mass spectra to known solution behavior. While the binding of many commercial monointercalators has been well-studied by ESI-MS, there has been only one study [20] that has focused on a bisintercalator, ditercalinium.…”
Section: Introductionmentioning
confidence: 99%